ANKAI SITELU: KOREOGRAFI TERINSPIRASI DARI SISTEM KEKERABATAN PADA MASYARAKAT KARO - DAMANIK, DESY WULAN PITA SARI (UNIVERSITAS STEKOM, 2023)
Ankai sitelu is taken from the Batak Karo language, the word ankai means understanding and sitelu which means sitiga. If these three words are interpreted, they mean a dance that originates from understanding rakut sitelu.